Measurements of the center-of-mass energies at BESIII via the di-muon process *Supported by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (11125525, 11235011, 11322544, 11335008, 11425524, Y61137005C), Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, CAS Center for Excellence in Particle Physics (CCEPP), Collaborative Innovation Center for Particles and Interactions (CICPI), Joint Large-Scale Scientific Facility Funds of NSFC and CAS (11179007, U1232201, U1332201), CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS, National 1000 Talents Program of China, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG (Collaborative Research Center CRC-1044), Istituto Nazionale di Fisica Nucleare, Italy, Ministry of Development of Turkey (DPT2006K-120470), Russian Foundation for Basic Research (14-07-91152), Swedish Research Council, U. S. Department of Energy (DE-FG02-04ER41291, DE-FG02-05ER41374, DE-FG02-94ER40823, DESC0010118), U.S. National Science Foundation, University of Groningen (RuG) and Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (June 2016) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Baldini Ferroli, R.; Ban 班, Y. 勇; et al.
Abstract: From 2011 to 2014, the BESIII experiment collected about 5 fb −1 data at center-of-mass energies around 4 GeV for the studies of the charmonium-like and higher excited charmonium states. By analyzing the di-muon process e + e − → γISR/FSR μ + μ −, the center-of-mass energies of the data samples are measured with a precision of 0.8 MeV. The center-of-mass energy is found to be stable for most of the time during data taking.